IMPLANTACIÓN DE UN SISTEMA CONTABLE EN EL COMERCIAL “JJ FLORES” DEL CANTÓN CATAMAYO, PROVINCIA DE LOJA, PERIODO: MARZO - JUNIO DEL 2016 - Agila Moreno, Tatiana Elizabeth (2017)
The present work of thesis entitled "IMPLEMENTATION OF A SYSTEM ACCOUNTING IN THE COMMERCIAL" JJ FLORES "OF CANTÓN CATAMAYO, PROVINCE OF LOJA, PERIOD: MARCH - JUNE 2016", has the purpose of implementing an Accounting System, Obtain real and timely information according to the commercial activities of the Commercial, capable of providing a significant contribution to the owner, for a good decision-making in the control and management of its economic. It should be noted that in order to comply with these proposed objectives, the inventory of goods began with a physical verification of the goods and values that the commercial possesses, which allowed to know the existing quantities of products for sale; Then the purchase and sale of merchandise was recorded, which allows analytical and orderly detail of transactions generated daily, the payable assistant that serves to record purchases on credit and payments made to suppliers, the assistant accountant Receivable that allows the detail of sales on credit and cash. The plan and manual of accounts were then elaborated according to the economic movement of the commercial. With this information, the State of Initial Situation was carried out in which it reflects the current situation with the beginning of this accounting year, with the memorandum of operations detailing the transactions generated daily to be recorded in the journal, summarizing The information in the general ledger, to move to the balance sheet and perform the worksheet with the respective adjustments, thus recording the results in the income statement, the statement of financial position and the cash flow statement 5 to finally perform the Application of the main financial indicators with their respective interpretations, evaluating the economic, financial and operational performance of the commercial. As for the methodology used, the materials and methods that were applied were presented and they helped to the theoretical knowledge and practical development, constituting the fundamental part for the fulfillment of the proposed objectives. At the conclusion of this research, the respective conclusions and recommendations are presented, demonstrating the reality and the need to implement an Accounting System to the Commercial "JJ FLORES", which is a guide to improve the organization and administration Of the company, which is why it is recommended to its owner to take into account the work of Thesis, which will be a contribution for the development and growth of your company.